PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TPS TERHADAP AKTIVITAS DAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMPN 3 PADANG - MEDIA KARNELA (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding of mathematical concepts is one of the cognitive abilities that are expected to be possessed by every student in learning mathematics. However, in reality it appears that understanding the mathematical concepts of students in class VIII of SMP 3 Padang is still low, so it needs to be improved. One effort to overcome this is by applying a learning model that can facilitate students in understanding the material and building their own knowledge. The learning model that can be applied is the TPS type cooperative learning model. Based on these problems, a research was conducted to describe whether the understanding of the mathematical concepts of students who learned using the TPS type cooperative learning model was better than the ability to understand the mathematical concepts of students using conventional learning models in class VIII SMP 3 Padang. This type of research is quasi-experimental with static group design. The results of this study indicate that the ability to understand the mathematical concepts of students who learn to apply the TPS model is better than the ability to understand the mathematical concepts of students whose learning implements conventional learning in class VIII SMP Negeri 3 Padang. Keywords – Understanding of mathematical concept,Think Pair Share, Conventional learning.